Hybrid of Boyer Moore and rule based system for mobile library book information - Hasan Basari, Abd Samad; Yusop, Noorezam; Hussin, Burairah; Shibghatullah, Abdul Samad (Foundation Of Computer Science (FCS), 2014)
In this paper, a hybrid of Boyer Moore and Rule Based System are introduced for library book information on mobile application. A hybrid approach is employed as solution to replace the Digital Resource, Web based Software System and Catalogue. Quick Response (QR) Code is an improvement to replace the barcode and it can access any sensor on mobile application. The methodology of this paper is to develop Library Book Information to be more effective and by combining Boyer Moore String Matching and Rule Based System. From the phase of Boyer Moore and Rule Based System, these are greatly simplified this system by using QR Code to get data in a real time. The result in Boyer Moore and Rule Based System shows with highest priority or threshold (maximum) to minimum. It can be concluded that the hybrid of Boyer Moore and Rule Based System can effectively support the library information system.